Visual content for community based tourism online marketing communication : A case study of Ban Nateen, Krabi province, Thailand - Thepthira Chaiinkham (Prince of Songkla University, 2021)
Thesis (M.B.A., (Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2019